Case report: Treatment with Phesgo® in a patient receiving hemodialysis - Pulido, Catarina; Albuquerque, Joana; Correia, Jorge; Passos-Coelho, José Luís (Frontiers in Oncology, 2024)
Patients with metastatic HER2-positive breast cancer have multiple therapeutic options, however, most are not studied in the renal replacement therapy (RRT) setting. Case report: We report the use of Phesgo® (subcutaneous fixed-dose combination ofcombined trastuzumab andplus pertuzumab) associated with exemestane, as a first-line treatment of metastatic HER2-positive breast cancer in a hemodialysis patient with multiple comorbidities. Partial response was attained, with disease progression after 8 months, without evidence of significant toxicity. Discussion: This case report is, to our knowledge, the first published case documenting the use of Phesgo® in a hemodialysis patient. No new safety signs were seen, and activity was documented, adding support to the use of this drug combination in such a patient population.